S24 Profile of the Airway Microbiome in COPD Using MALDI-TOF. (19th November 2012) - Thurston, SJ; McHugh, TD; Donaldson, GC; Wedzicha, JA
Abstract : Introduction: Bacterial infections are well known to have an association with chronic obstructive pulmonary disease (COPD), with Streptococcus pneumoniae, Haemophilus influenzae and Moraxella catarrhalis often seen at exacerbation. Many microbiome studies have relied on molecular methods which can be prolonged and expensive. The use of matrix-assisted laser desorption/ionisation-time of flight (MALDI-TOF) offers an efficient and economical approach to the evaluation of the airway microbiome, necessary to increase knowledge of the role of the microbial community in COPD. Aims: To identify the range and diversity of bacteria which form the airway microbiome in COPD To consider whether the MALDI-TOF is an appropriate method for this study. Methods: 44 patients from the London COPD cohort produced 65 sputum samples at baseline and exacerbation mean (±SD) age 73.7 years (±9.4); predicted FEV1 50.7% (±18.12); male gender 77.5%; exacerbation samples 47.7%. Sputum samples are initially sent to the NHS Royal Free Trust microbiology lab where traditional culture methods are performed. Once processed the agar plates were collected and different colonies are spotted onto target plates and loaded onto the MALDI-TOF MALDI-TOF profile spectrum is then generated allowing for data interpretation. Isolates that were defined as pathogenic were removed from the data with those classified as typical bacteria were then included separately. Results: Streptococcus, Staphylococcus, Rothia and Neisseria are the most dominant genera seen in baseline and exacerbation NRTF samples at the genus level contributing to 85, 28, 20 and 18 percent respectively. MALDI-TOF identified 25 NRTF groups at genus level in the COPD samples. In the typical pathogenic genus groups Haemophilus is the most dominant group identified by this method. Conclusion: The MALDI-TOF identifies a diverse bacterial range in COPD patients including pathogenic organisms and those defined as NRTF The MALDI-TOF is quick and inexpensive, as well as efficient which is an advantage over molecular assays.